Design and implementation of a semi-automatic gate - Olivier, Hakizabera; Claude, Kwizera Jean; Emmanuel, Uwayezu (Review of Industrial Engineering Letters, 2023)
The semi-automatic gate is mainly used in industries, schools, Hotels, etc. A design for the semi-automation sliding gate with electrical energy has been designed and implemented at RP IPRC-Kigali. The project aims to fabricate a simple model to show how the system would ensure students’ punctuality in secondary schools. We use a rack and pinion mechanism for sliding the gate forward and reverse in this proposed method. It also mainly consists of design aspects such as stress analysis, load management, design for the selection of material, size of material, etc. When we press the open button, a signal is sent to the main circuitry board, allowing the current to pass through to the gate motor, causing the motor to run and open. Once the gate is fully open (depending on where the resistant beam is located), the motor stops running, causing the gate to stop moving. When the bearing steps on the close button are pressed, the same thing happens, but this time, the motor runs in the opposite direction, causing the gate to close. The motor was able to move the gate from one end to the other smoothly with the push of a button. It is safer and more secure compared to manual gates used in secondary schools and it can keep the people who live in the compound safe.